A Survey on Energy-Aware Wireless Sensor Routing Protocols - Mittal, Mohit; Iwendi, Celestine (EAI Endorsed Transactions on Energy Web, 2019)
A technological evolution in digital electronics gives birth to micro-electro-mechanical systems (MEMS). This evolution generates drastic change in the field of micro-sensors. Micro-sensors are advanced in capabilities of low-cost, less energy consumption, self-configurable, work on heterogeneous environment and highly reliable. A way to work efficiently automated systems are relying on sensor backbone known as routing protocols. The routing protocols is key whose functionality provides a better usability of a system in effective and efficient way. In this paper, we have focused on categories of routing protocols based on required applications. The main idea of this survey to present the applicability of sensor routing protocols in various indoor and outdoor applications.
Keywords: energy efficient; sensor routing protocols; clustered sensor routing; fuzzy logic sensor routing; swarm intelligence sensor routing